1992
DOI: 10.1002/lsm.1900120406
|View full text |Cite
|
Sign up to set email alerts
|

Holmium‐laser synovectomy of immune synovitis in rabbits

Abstract: Holmium-laser synovectomy was carried out to remove allergically inflamed synovial membranes in rabbit knee joints. The healing process was then investigated at different periods. Left knee joints of 12 rabbits were exposed to Ho:YAG-laser radiation at a wavelength of 2.1 microns, pulse energy of 600 mJ, pulse length of 1 ms, and repetition rate of 3 Hz. Twelve others were treated conventionally and 12 served as controls. After 1 day, 1 week, and 1 and 3 months, respectively, 3 animals from each group were sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This difference can be explained by the decreased degree of immunosensitization used in our study, compared with the degree used in other studies. Other investigators 18,19,25 identified substantial effusion, lameness, and gross pathologic changes following immunosensitization. Investigators in those studies administered 2 doses of ovalbumin, ID, prior to intraarticular injection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference can be explained by the decreased degree of immunosensitization used in our study, compared with the degree used in other studies. Other investigators 18,19,25 identified substantial effusion, lameness, and gross pathologic changes following immunosensitization. Investigators in those studies administered 2 doses of ovalbumin, ID, prior to intraarticular injection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had a design similar to that of other studies 17,19 in which investigators used antigen-induced arthritis in rabbits to evaluate various modalities of surgical synovectomy. However, complications encountered in our study differed from those in the other reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excimer lasers can be used via an arthroscope, but ablation rates are too low [10]. At present, the best laser system for arthroscopic application seems to be the Ho:YAG, which combines a high ablation rate with acceptable thermal side effects and the possibility of using it in a fluid medium [11][12][13]. But even with the Ho:YAG laser, synovectomy is more time-consuming than with a mechanical device.…”
Section: Introductionmentioning
confidence: 99%